Modal Sosial Sebagai Properti Individu: Konsep, Dimensi Dan Indikator - Tjahjono, Heru Kurnianto (Universitas Muhammadiyah Yogyakarta, 2017)
Social Capital is a broad concept and often defined ambiguously. A number of literatures indicate that social capital can be seen at various levels of analysis, either at macro, organizational, group or individual level. This study sees that social capital is a concept that becomes an individual property. The purpose of this study was to operationalize social capital into dimensions and indicators at the level of individual analysis. This study starts from a literature study followed by a focus group discussion involving four graduate master of science in Organizational Psychology. The next stage is to test the instruments to the field by involving employees. The results show that social capital includes 3 dimensions (structural, relational and cognitive) and 12 core indicators.